Hubungan Antara Persepsi Harga dan Keputusan Pembelian Konsumen di Kopi Tuku : Studi Akuntansi Konsumen - Septi Setyaningsih; Nadia Zahra Faisal; Afiyah Lucahya; Nahwa Janah; Nabila Najwa; Husni Mubarok (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to examine consumers' perceptions of price influence their decision to purchase local coffee brand Kopi Tuku. Price perception is regarded as a key element influencing purchasing decisions, as consumers tend to judge price based on its quality, benefits, and nominal value. This study conducted quantitative research by surveying 395 Kopi Tuku consumers. Validity, reliability, classical assumptions, simple linear regression analysis, and t and F tests were used. The findings indicated that price perception significantly influences purchase decisions, as demonstrated by a computed value of 22.006 that is higher than the t-table and a significance value of 0.000. In addition,the value of 0.552 for the coefficient of determination (R²) indicates that price perception is responsible for 55.2% of the variation in purchasing decisions. The results suggest that in order to increase customer purchasing choices, Kopi Tuku should maintain a pricing strategy that is reasonable, competitive, and aligned with the worth of the available goods.